A novel quadruple-spaced multiwavelength Brillouin-erbium fiber laser. (1st October 2021) - Xu, Ronghui; Zhang, Xianqiang; Xue, MinMin; Chen, Ming; Cheng, Yu; Deng, Hongchang; Deng, Shijie; Liu, Houquan; Teng, Chuanxin; Yang, Hongyan; Qu, ShiLiang; Yuan, Libo
Abstract: We demonstrated a compact multiwavelength Brillouin-erbium fiber laser (MBEFL) with quadruple-Brillouin-frequency spacing. The quadruple-Brillouin-frequency spacing multiwavelength is generated mainly by utilizing two four-port circulators, two coils of single-mode fiber and two erbium gain modules. The generated multiwavelength spectra were investigated through adjusting the Brillouin pump (BP) and the 980 nm pumps. In the experiments, eight stable wavelengths were produced and the wavelength spacing was 0.348 nm (about 43.5 GHz) as the wavelength and the power of the BP were 5 mW and 1548.11 nm respectively, meanwhile the two 980 nm pumps' powers were 470 mW and 520 mW respectively. The output multiwavelength can be tuned from 1546.12 nm to 1561.01 nm, and the maximum optical signal-to-noise ratio (OSNR) of the output channel was about 37 dB. The average OSNR of the stable multiwavelength was about 27 dB. The proposed stable and wider channel spaced MBEFL has diverse applications in dense wavelength division multiplexing optical communication, microwave photonics and fiber-optic sensors.